2018
DOI: 10.1002/adma.201705400
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Flexible Visual Memory System Based on an UV‐Motivated Memristor

Abstract: For the mimicry of human visual memory, a prominent challenge is how to detect and store the image information by electronic devices, which demands a multifunctional integration to sense light like eyes and to memorize image information like the brain by transforming optical signals to electrical signals that can be recognized by electronic devices. Although current image sensors can perceive simple images in real time, the image information fades away when the external image stimuli are removed. The deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
340
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(360 citation statements)
references
References 35 publications
1
340
0
Order By: Relevance
“…

away quickly when the light stimuli are removed. [6][7][8][9] For example, a bioinspired visual system comprising an In 2 O 3 nanowire photodetector connected in series with an Al 2 O 3 memristor was fabricated recently, which could capture a butterflyshaped image and store it for more than 1 week. To realize both detection and memory functions so as to better imitate the human visual system, researchers have attempted to integrate the photodetectors with the nonvolatile memory devices.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…

away quickly when the light stimuli are removed. [6][7][8][9] For example, a bioinspired visual system comprising an In 2 O 3 nanowire photodetector connected in series with an Al 2 O 3 memristor was fabricated recently, which could capture a butterflyshaped image and store it for more than 1 week. To realize both detection and memory functions so as to better imitate the human visual system, researchers have attempted to integrate the photodetectors with the nonvolatile memory devices.

…”
mentioning
confidence: 99%
“…[3][4][5] In other words, traditional photodetectors can detect the images like a retina, but they lack the memory function owned by the visual cortex (see schematic illustration of human visual system in Figure 1a). [9] In such integrated devices, however, the units responsible for detection, processing, and storage of optical information are physically separated, resulting in high power consumption for data transfer between different units (just as the Von Neumann bottleneck [10,11] ).A simple yet effective humanoid optoelectronic device emerging recently is the artificial optoelectronic synapse based on the photoelectric memristor, which can co-locate the detection and memory functions in a single unit. [6][7][8][9] For example, a bioinspired visual system comprising an In 2 O 3 nanowire photodetector connected in series with an Al 2 O 3 memristor was fabricated recently, which could capture a butterflyshaped image and store it for more than 1 week.…”
mentioning
confidence: 99%
“…Studies have shown that light can control Ca 2+ concentration ([Ca 2+ ] i ) in intracellular with a light‐gated Ca 2+ ion channels to control the influx of Ca 2+ , thereby modulating the synaptic plasticity behaviors . Previously, diverse memristors that can be controlled by a light stimulation have been suggested and investigated . As remarkable light absorbing materials, OHP‐based memristors offer the the potential of high‐order tuning of the synaptic plasticity.…”
Section: Memristors Based On Ohpsmentioning
confidence: 99%
“…[3,[29][30][31] Among these polymer substrates, PI has high tensile strength, very low creep, and great flexibility which can also be used at a temperature of 452 °C. Various polymer films, including polycarbonate, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polyimide (PI), have been developed as substrates for electronic devices and soft electrodes because of their great mechanical, good chemical resistance, and thermal stability.…”
Section: Flexible/stretchable Substratementioning
confidence: 99%